Multilateral Official Debt Rescheduling : Recent Experience, November 1990 - Guzman, Jorge (World Economic and Financial Surveys; World Economic and Financial Surveys, 1990)
This paper reviews trends in official debt rescheduling and recent experience with debt renegotiations in the face of the persistent problems of heavily indebted developing countries.